Pengembangan Tes Sumatif Online Berbasis Progressive Web App Terhadap Proses Ujian (Studi Kasus : Jakarta Global University) - Onki Alexander; Untung Suprihadi; Risma Ekawati (STMIK IKMI Cirebon, 2021)
The benefits of a web-based application make web developers improve the quality of their applications, one of which is implementing a Progressive Web App (PWA). Researchers see the potential of web-based summative test applications at Jakarta Global University (JGU) which have been designed by previous researchers to be developed by implementing PWA. This study aims to develop a web-based online summative test system/application to be PWA-based. PWAs combine the best of the web with the features native apps already have. The benefits of this research can be used as input or reference for JGU in developing more optimal web applications for campus needs. The development in this system applies the public server and PWA methods. Unified Modeling Language (UML) for system design. PWA testing using the Lighthouse tool. The results obtained from this study are in the form of a PWA-based online test summative system with the ability to be accessed on desktop and mobile and the ability to be accessed offline.